2012
DOI: 10.1111/j.1600-048x.2012.05665.x
|View full text |Cite
|
Sign up to set email alerts
|

Declining egg viability explains higher hatching failure in a suburban population of the threatened Florida scrub‐jay Aphelocoma coerulescens

Abstract: Hatching failure occurs in approximately 10% of all avian eggs, but varies both within and among species. This reduction in viable offspring can have significant fitness consequences for breeding parents; therefore, it is important to understand which factors influence variation in hatching failure among populations. Previous research suggests that hatching failure is higher in a suburban than in a wildland population in the Florida scrub‐jay. From 2003 to 2007, we performed two experiments to examine whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The curves are merely conceptual based on the literature and do not represent a formal meta-analysis. Curves exhibiting extreme changes in mortality rates (such as vehicles) represent the "strength" (or consistency) of the pattern among studies, whereas a slight curve (such as disease) reflects mixed results and a more complex relationship with urbanization in suburban areas (Schoech and Bowman 2003;Fleischer et al 2003), advanced laying dates resulted in greater hatching failures due to increased exposure of eggs to low ambient temperatures (Aldredge et al 2012). While most studies have demonstrated advanced phenology of residents and short-distance migratory birds in cities (Eden 1985;Antonov and Atanasova 2003;Schoech and Bowman 2003), urban birds also may initiate breeding later.…”
Section: Phenologymentioning
confidence: 98%
“…The curves are merely conceptual based on the literature and do not represent a formal meta-analysis. Curves exhibiting extreme changes in mortality rates (such as vehicles) represent the "strength" (or consistency) of the pattern among studies, whereas a slight curve (such as disease) reflects mixed results and a more complex relationship with urbanization in suburban areas (Schoech and Bowman 2003;Fleischer et al 2003), advanced laying dates resulted in greater hatching failures due to increased exposure of eggs to low ambient temperatures (Aldredge et al 2012). While most studies have demonstrated advanced phenology of residents and short-distance migratory birds in cities (Eden 1985;Antonov and Atanasova 2003;Schoech and Bowman 2003), urban birds also may initiate breeding later.…”
Section: Phenologymentioning
confidence: 98%
“…Rather than being affected by urbanization, CORT levels seem to be more dependent on species, sex, life-history stage, or even morphs studied. A good example to illustrate this lack of pattern comes from analyses of CORT levels in urban and rural house sparrows from three different cities: Phoenix (USA), Budapest (1998), Leston & Rodewald (2006), Marzluff & Neatherlin (2006), Rodewald & Shustack (2008a,b), Whittaker & Marzluff (2009) Laying date 10 (5) 7 (7) 3 (2) Eden (1985), Antonov & Atanasova (2003), Mennechez & Clergeau (2006), Hinsley et al (2008), Newhouse et al (2008), , Aldredge et al (2012), Stracey & Robinson (2012), Brahmia et al (2013), Strasser & Heath (2013), Solonen (2014), Solonen & Hilden (2014), Sumasgutner et al (2014), Lin et al (2015), Wawrzyniak et al (2015), Bailly et al (2016), Sprau et al (2016), Vaugoyeau et al (2016) attendance in eight different bird species, nest attendance was higher in four (Table S7), did not differ in three and was lower in one study with a small sample size (nine lesser kestrel, Falco naumanni nests, Liven-Schulman, Leshem, Alon, & Yom-Tov, 2004). This was sometimes associated with less quality food for offspring (e.g.…”
Section: Stress Levelmentioning
confidence: 99%
“…While observational and experimental work point toward the ready access of human‐source foods in the suburban environment as the primary driver of the earlier reproduction, numerous other factors might also contribute (Schoech and Bowman, ). Potential factors experienced in a suburban versus a natural habitat that could be stimulatory include increased: (1) temperature due to an “urban heat island” effect (e.g., Fan and Sailor, ; for site‐specific data see Aldredge et al, ); (2) predictability of food resources (i.e., knowing where food can be obtained at any time on a year‐round basis, such as a pet food dish, see Bridge et al, ); and (3) exposure to artificial lighting at night from street lamps and houses.…”
mentioning
confidence: 99%